2021
DOI: 10.1039/d1dt02251b
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared light-responsive photothermal α-Fe2O3@Au/PDA core/shell nanostructure with on–off controllable anti-bacterial effects

Abstract: Antimicrobial materials are expected to be alternatives for antibiotics against multidrug-resistant bacteria. In this paper, the non-spherical "α" -Fe2O3@Au/PDA core/shell nanoparticles with tunable shapes are synthesized by a one-step in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…As a result, we confirmed that the as-synthesized sec D3Ds are three-dimensional in nature. Because of the rodlike (or spindle ,, ) characteristic of each branch, we further determined the structural thickness to be around 229 nm, consistent with a prior study . It has been previously suggested that the branch or so-called sub-branch with a rodlike shape is the fundamental building block of the entire dendritic or fractal structure.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…As a result, we confirmed that the as-synthesized sec D3Ds are three-dimensional in nature. Because of the rodlike (or spindle ,, ) characteristic of each branch, we further determined the structural thickness to be around 229 nm, consistent with a prior study . It has been previously suggested that the branch or so-called sub-branch with a rodlike shape is the fundamental building block of the entire dendritic or fractal structure.…”
Section: Resultssupporting
confidence: 57%
“…The hydro/solvothermal synthesis of branched and dendritic α-Fe 2 O 3 structures was optimized based on the concepts of prenucleation, facet-directed growth fractal, , acidity/basicity, and the solvent’s boiling point, polarity, and viscosity. All synthetic variants of the branched α-Fe 2 O 3 , as-synthesized via the hydro/solvothermal reaction of 4 mM K 3 [Fe­(CN) 6 ] with a controlled reaction temperature for 20 h, were summarized in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…4 C). Both S. aureus and E. coli with PBS treatment showed smooth and intact cell membranes, indicating negligible damage to bacteria from PBS [ 49 ]. In contrast, the bacteria were damaged to varying degrees after the hydrogel and hydrogel ​+ ​NIR treatments.…”
Section: Resultsmentioning
confidence: 99%
“…5d. 38,39 The above results suggest that PSS modified PLNP-Bi 2 S 3 composite nanoplatforms have good photothermal conversion performance.…”
Section: Dalton Transactions Papermentioning
confidence: 80%